Spatio-Temporal Shoreline Movement of the Afram River in Ghana: The Application of Endpoint Rate and Net Shoreline Movement - Aninakwah Isaac; Kofi Adu- Boahen; Ishmael Yaw Dadson (Journal Of Social Science (JoSS), 2023)
Shoreline change is a severe threat to life and property in wetland regions. Shoreline change analysis is critical for integrated wetland zone management and is accomplished through the field and aerial surveys. The Afram River is a significant source of water, food, and economic activity for Kwahu and its neighbouring communities and a form of funds for the residents. The shoreline, nevertheless, has been transforming because of erosion and accretion. This study examined a low-cost innovative approach using space-based peripheral visuals and metrics. Transects and data analysis for the riverbank were created using the Digital Shoreline Analysis System (DSAS) in the Spatial database. The study employed Landsat images from three historical years (2001, 2015 and 2022) across 22 years. End Point Rate (EPR) and Net Shoreline Movement (NSM) statistics in DSAS were used to determine the extent of change. Questionnaires and key informant interviews were administered to farmers, boat operators, fishermen, and older residents to learn more about the factors responsible for changes in shoreline position. According to the study, 24% of the shoreline erodes at a section, while 86% is stable. The survey's mean erosion rate is -0.24 m/yr, whereas the average accretion proportion is 27 m/yr. The ramifications of the Afram River channel change have affected the socio-economic livelihoods, including out-migration, farm loss and displacement of settlement. As a result, all organisations and participants responsible for these riverbanks should work together to prevent further damage and erosion of the shoreline line and its marine life and resources.